Enhanced sheet-sheet welding and interfacial wettability of 3D graphene networks as radiation protection in gamma-irradiated epoxy composites. (22nd March 2018) - Wang, Haibo; Li, Nan; Xu, Zhiwei; Tian, Xu; Mai, Wei; Li, Jing; Chen, Cheng; Chen, Lei; Fu, Hongjun; Zhang, Xingxiang
Abstract: 3D graphene networks (3DGN) as reinforcement for epoxy composites have attracted intense attention, while the interfacial adhesion with the matrix is still a key issue. With respect to the impact between interfacial wettability for graphene sheets in 3DGN and the performance for epoxy-based composites, 3DGNs prepared by self-assembly method, have been carbonized in N2 at heat treatment temperature between 220 and 800 °C, and then incorporated into epoxy by resin transfer molding method. Polyving akohol serving as cross-linking agent is converted to amorphous carbon during the annealing process, which effectively interconnects and enhances graphene sheet-sheet welding. When the carbonization temperature is 400 °C (3DGN-4), epoxy contact angles decrease from 100.2° to 56.7°, and 3DGN-4/epoxy composites are increased significantly 84% and 56% in compressive and flexural strength, respectively. In the meantime, this 3DGN serving as radiation protection of epoxy composites has been investigated for the first time. The electron spin resonance detection shows that 3DGN could act as radical scavenger in the gamma irradiation environment, and mechanical performance retention rate of 3DGN-4/epoxy composites is above 92% after gamma irradiation, which is higher than that of epoxy resin. Therefore, the designed 3D graphene networks can be considered as promising candidates for improving both the mechanical properties and radiation resistance of epoxy composites.